Sign-Changing Solutions for a Fourth-Order Elliptic Equation with Hardy Singular Terms - Ruichang Pei; Jihui Zhang (Journal of Applied Mathematics)
The existence and multiplicity of sign-changing solutions for a class of fourth elliptic equations with Hardy singular terms are established by using the minimax methods.